Advances in Skeletal Muscle Health and Disease - Arturo Iannotti, Fabio (Physiology, 2023)
Skeletal muscles are the vastest tissue in the human body with an essential role in maintaining posture, moving, and regulating internal body temperature and metabolism. Consequently, skeletal muscle injuries or diseases can have a profound effect on one's life. In Advances in Skeletal Muscle Health and Disease, Fabio Arturo Iannotti has assembled contributions from international experts to provide a conclusive guide to what continues to be a rapidly developing research field. After a short introductory chapter, the book continues by looking at the biochemical, genetic, and molecular elements and mechanisms underlying skeletal muscle health and disease.